How do you simplify #(8a^2-6a-9)/( 6a^2-5a-6) ÷ (4a^2+11a+6)/( 9a^2+12a+4)#?

1 Answer
Mar 29, 2018

Answer:

#(3a+2)/(a+2)#

Explanation:

#{(8a^2-6a-9)/(6a^2-5a-6)}-: {(4a^2+11a+6)/(9a^2+12a+4)}#

#={(8a^2-12a+6a-9)/(6a^2-9a+4a-6)}-: {(4a^2+8a+3a+6)/(9a^2+6a+6a+4)}#

#={(4a(2a-3)+3(2a-3))/(3a(2a-3)+2(2a-3))}-: {(4a(a+2)+3(a+2))/(3a(3a+2)+2(3a+2))}#

#={(cancel((2a-3))(4a+3))/(cancel((2a-3))(3a+2))}-: {((a+2)(4a+3))/((3a+2)(3a+2))}#

#=cancel((4a+3))/cancel((3a+2))*(cancel((3a+2))(3a+2))/((a+2)cancel((4a+3)))#

#(3a+2)/(a+2)# [Ans]